“The COVID-19 Murders”: Prison death-worlds and the fatal convenience of crisis - Lackey, Dalton J (Punishment & society, 2025)
Since the eruption of the COVID-19 pandemic, U.S. correctional facilities have reported more than half a million positive cases and nearly 3000 deaths. The carceral regime's unconscionable response to COVID-19 has been accepted as a mere “failure” by observers. We question this reading given the dispossessing purpose of carceral punishment, instead reframing prisons as necropolitical death-worlds that weaponize crisis to advance their repressive capacities. We draw from 132 texts authored by 68 incarcerated witnesses and published by the American Prison Writing Archive to assess how incarcerated individuals experience and interpret both the COVID-19 pandemic and the mitigation efforts enacted by prison administrations. Rather than prisons struggling, sincerely, to slow the spread of COVID-19, witnesses call attention to how prisons constrict and evolve punishment under the guise of care. Sampled writings detail alarming changes, including the excessive application of already harmful practices like solitary confinement. Our findings speak to the “inside,” lived implications of disaster-response by death-worlds, where the necropolitical order practices and perfects its violence with little external protest. Scholars of carceral punishment should more deliberately consider the impact of crises like the pandemic, as it is certainly not the last disaster that the prison order will appropriate.